Outcome of dual mobility total hip arthroplasty in patients who are at high risk for dislocation - Kyavater, Basavaraj S.; M. D., Rafeeq; Kumar, Sathish; Hallinalli, Hemanth P. (International Journal of Research in Orthopaedics, 2021)
Background: Dislocation after total hip arthroplasty (THA) remains a major concern, because it is reported to range from 1% to 5%. The concept of dual mobility articulation was developed in 1970 by Bousquet to decrease dislocation risk. Several studies have looked at the outcome of dual mobility articulation in primary THA and in revision THA. Methods: This is a prospective study of 33 patients undergoing dual mobility THA during 24 months period from October 2017 to September 2019. Patients undergoing total hip replacement (THR) to have dual mobility cup (DMC) were those at high risk of dislocation. Patients were followed up for a mean period of 18 months. Results: 33 patients (mean age 67 years) underwent DMC THA. 27 patients underwent primary hip replacement. The follow-up of our cases has ranged from 13 months to 3 years with a mean follow-up of 18 months. none of the patients had hip dislocation. Conclusions: The DMC is an effective solution for the management of high-risk cases undergoing total hip replacement to reduce the incidence of postoperative instability.